2011
DOI: 10.1088/0967-3334/32/8/011
|View full text |Cite
|
Sign up to set email alerts
|

Regional coherence evaluation in mild cognitive impairment and Alzheimer's disease based on adaptively extracted magnetoencephalogram rhythms

Abstract: Abstract. This study assesses the connectivity alterations caused by Alzheimer's disease (AD) and mild cognitive impairment (MCI) in the magnetoencephalogram (MEG) background activity. Moreover, a novel methodology to adaptively extract brain rhythms from the MEG is introduced. This methodology relies on the ability of an Empirical Mode Decomposition (EMD) to isolate local signal oscillations and a constrained Blind Source Separation (cBSS) to extract the activity that jointly represents a subset of channels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 46 publications
(205 reference statements)
3
46
0
1
Order By: Relevance
“…Thus, an early AD diagnosis should be established on the basis of a previous MCI detection. Our findings suggest that MCI exhibit intermediate alterations between AD and normal aging, which agrees with the results of previous research (Fernandez et al 2006, 2010, Escudero et al 2011. Previous MEG studies reported classification rates of AD patients versus elderly controls about 80% (Fernandez et al 2006, Poza et al 2007, Gomez et al 2009a, Hornero et al 2009, Stam 2010, Alonso et al 2011, Escudero et al 2011.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, an early AD diagnosis should be established on the basis of a previous MCI detection. Our findings suggest that MCI exhibit intermediate alterations between AD and normal aging, which agrees with the results of previous research (Fernandez et al 2006, 2010, Escudero et al 2011. Previous MEG studies reported classification rates of AD patients versus elderly controls about 80% (Fernandez et al 2006, Poza et al 2007, Gomez et al 2009a, Hornero et al 2009, Stam 2010, Alonso et al 2011, Escudero et al 2011.…”
Section: Discussionsupporting
confidence: 92%
“…Our classification results are similar to this value, since the highest accuracy was 83.9%. On the other hand, previous MEG studies usually reached an accuracy about 65% to discriminate between MCI and control subjects (Fernandez et al 2006, 2010, Gomez et al 2009a, Escudero et al 2011. Our highest accuracy was 65.9%.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Decreasing posterior alpha power in MCI patients (Babiloni et al, 2008), gray matter loss in temporal, parietal, and frontal regions (Karas et al, 2004;Barbeau et al, 2008) and increased activity of occipital regions in MCI subjects during incremental learning (Moulin et al, 2007) are some of the major findings previously reported. Although there are some studies on functional connectivity of MCI's brain (Gómez et al, 2009;Escudero et al, 2011), only a few researchers have investigated the global organization of brain networks in MCI (de Haan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%